Design and Validation of a Trauma-Informed Curriculum Model for Enhancing Resilience and Mental Health among Students in Post-Crisis Conditions - Akbarzadeh Sagay , Mehdi; Kangari, Fatemeh; Allahabady, Saeedeh; Riazi, Fatemeh; Mohaddes, Nasrin (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to design and validate a trauma-informed curriculum model for enhancing resilience and mental health among students in post-crisis educational conditions. The study was conducted using a mixed-methods exploratory sequential design in Tehran during the 2025–2026 academic year. In the qualitative phase, semi-structured interviews were conducted with 18 experts in curriculum planning, educational psychology, counseling, and crisis intervention selected through purposeful sampling until theoretical saturation was achieved. The qualitative data were analyzed using thematic analysis to identify the dimensions and components of the trauma-informed curriculum model. In the quantitative phase, the proposed model was validated among 312 educational professionals, including teachers, counselors, school administrators, and curriculum specialists selected through multistage cluster sampling. Data collection instruments included the Connor–Davidson Resilience Scale, the General Health Questionnaire, and a researcher-developed Trauma-Informed Curriculum Questionnaire derived from the qualitative findings. Descriptive statistics, exploratory factor analysis, confirmatory factor analysis, and structural equation modeling were conducted using IBM SPSS Statistics and AMOS software. The findings demonstrated that the proposed trauma-informed curriculum model possessed acceptable construct validity and strong structural fit indices (χ²/df = 2.14, RMSEA = 0.059, CFI = 0.95, GFI = 0.93). Exploratory factor analysis extracted seven dimensions including emotional safety, supportive teacher–student relationships, flexible instructional practices, crisis-sensitive evaluation, psychosocial support systems, resilience-building educational activities, and school climate responsiveness, explaining 68.47% of the total variance. Structural equation modeling revealed that psychosocial support (β = 0.45), emotional safety (β = 0.41), and supportive relationships (β = 0.37) significantly predicted student resilience. In addition, school climate responsiveness (β = 0.39), flexible instruction (β = 0.31), and crisis-sensitive evaluation (β = 0.28) significantly predicted mental health outcomes. The overall model explained 57% of the variance in resilience and 52% of the variance in mental health among students in post-crisis conditions. The findings indicate that trauma-informed curriculum design can function as an effective educational and psychosocial framework for strengthening resilience and promoting mental health among students exposed to crises and traumatic experiences. The integration of emotionally supportive environments, psychosocial services, flexible pedagogical practices, and responsive school climates into curriculum structures may significantly improve students’ psychological adaptation and educational functioning during post-crisis recovery. The study highlights the necessity of incorporating trauma-informed principles into educational policy, curriculum development, teacher training, and school support systems to enhance the long-term well-being of students in increasingly crisis-prone societies.